The rise and fall of strategic planning - Mintzberg, Henry. (Prentice Hall, 1994)
This book presents about planning and stratery; models of the Strategic Planning Process; Evidence on Planning; Some real Pitfalls of Planning; Fundamental Fallacies of Strategic Planning...